Towards instantaneous cellular level bio diagnosis: laser extraction and imaging of biological entities with conserved integrity and activity. (26th June 2015) - Ren (任伶), L; Robertson, W D; Reimer, R; Heinze, C; Schneider, C; Eggert, D; Truschow, P; Hansen, N-O; Kroetz, P; Zou (邹晶), J; Miller, R J D
Abstract: The prospect for spatial imaging with mass spectroscopy at the level of the cell requires new means of cell extraction to conserve molecular structure. To this aim, we demonstrate a new laser extraction process capable of extracting intact biological entities with conserved biological function. The method is based on the recently developed picosecond infrared laser (PIRL), designed specifically to provide matrix-free extraction by selectively exciting the water vibrational modes under the condition of ultrafast desorption by impulsive vibrational excitation (DIVE). The basic concept is to extract the constituent protein structures on the fastest impulsive limit for ablation to avoid excessive thermal heating of the proteins and to use strongly resonant 1-photon conditions to avoid multiphoton ionization and degradation of the sample integrity. With various microscope imaging and biochemical analysis methods, nanoscale single protein molecules, viruses, and cells in the ablation plume are found to be morphologically and functionally identical with their corresponding controls. This method provides a new means to resolve chemical activity within cells and is amenable to subcellular imaging with near-field approaches. The most important finding is the conserved nature of the extracted biological material within the laser ablation plume, which is fully consistent with in vivo structures and characteristics.